2017
DOI: 10.3389/fpsyg.2017.01359
|View full text |Cite
|
Sign up to set email alerts
|

Systems Perspective of Amazon Mechanical Turk for Organizational Research: Review and Recommendations

Abstract: Amazon Mechanical Turk (MTurk) is becoming a prevalent source of quick and cost effective data for organizational research, but there are questions about the appropriateness of the platform for organizational research. To answer these questions, we conducted an integrative review based on 75 papers evaluating the MTurk platform and 250 MTurk samples used in organizational research. This integrative review provides four contributions: (1) we analyze the trends associated with the use of MTurk samples in organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
222
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(233 citation statements)
references
References 135 publications
10
222
1
Order By: Relevance
“…We recruited a sample of 1,030 U.S. employed individuals using the Prolific Academic crowd‐sourcing platform for a web‐based survey (https://prolific.ac). Prolific is similar to the Amazon Mechanical Turk (MTurk) platform, which has seen widespread use in organizational research (Keith, Tay, & Harms, ). However, Prolific participants have been found to be more naïve, less dishonest, more diverse, and to provide data of similar quality compared to MTurk participants (Peer, Brandimarte, Sama, & Acquisti, ).…”
Section: Methodsmentioning
confidence: 99%
“…We recruited a sample of 1,030 U.S. employed individuals using the Prolific Academic crowd‐sourcing platform for a web‐based survey (https://prolific.ac). Prolific is similar to the Amazon Mechanical Turk (MTurk) platform, which has seen widespread use in organizational research (Keith, Tay, & Harms, ). However, Prolific participants have been found to be more naïve, less dishonest, more diverse, and to provide data of similar quality compared to MTurk participants (Peer, Brandimarte, Sama, & Acquisti, ).…”
Section: Methodsmentioning
confidence: 99%
“…We recruited a convenience sample of gamblers by using MTurk. Some research has shown that MTurk samples are not representative of the American general population-these samples tend to be younger, more educated, and lower on the income scale (for a review, see Keith, Tay, & Harms, 2017). That said, samples drawn from MTurk are more demographically diverse and representative of the general population than student-based samples are (Buhrmester, Kwang, & Gosling, 2011).…”
Section: Limitationsmentioning
confidence: 99%
“…If prescreening is not possible, but genuine eligibility can be ensured using data managed by the online platform being utilized, it should be considered worthwhile, even at extra cost. Also, even though the current study focused on the possible harms of explicitly listing eligibility criteria, other complementary steps should be taken to maximize the validity of data collected on MTurk (e.g., attention checks; see Keith et al, for a discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of using Amazon’s Mechanical Turk (MTurk) for data collection continues to grow within academic communities (e.g., Bowen, Daniel, Williams, & Baird, ; Chan & Holosko, ; Goodman, Cryder, & Cheema, ; Gosling & Mason, ; Mason & Suri, ; see Sheehan, for a review). Accordingly, there have been numerous reviews of MTurk, its utility, and ways of maximizing data integrity (e.g., Jia, Steelman, & Reich, ; Keith, Tay, & Harms, ). These reviews note several benefits, including the often‐described utility of allowing scholars to access hard to reach populations (Smith, Sabat, Martinez, Weaver, & Xu, ; see Chandler & Paolacci, for a list of various examples).…”
Section: Introductionmentioning
confidence: 99%